ANÁLISE DO CONHECIMENTO E CUIDADOS DE TRABALHADORES RURAIS REFERENTE - Loro, Marli M.; Stumm, Eniva M. F.; Kierchner, Rosane M.; Zaisov, Alexandre; Bortolon, Mariela; Bezarra, Elisa L. (Salão do Conhecimento, 2013)
Resumo